2023
DOI: 10.1017/s1049023x23006519
|View full text |Cite
|
Sign up to set email alerts
|

Application of Telemedicine in the Ambulance for Stroke Patients: A Systematic Review

Fatemeh Sarpourian,
Milad Ahmadi Marzaleh,
Seyed Ali Fatemi Aghda
et al.

Abstract: Introduction: The use of telemedicine for the prehospital management of emergency conditions, especially stroke, is increasing day by day. Few studies have investigated the applications of telemedicine in Emergency Medical Services (EMS). A comprehensive study of the applications of this technology in stroke patients in ambulances can help to build a better understanding. Therefore, this systematic review was conducted to investigate the use of telemedicine in ambulances for stroke patients in 2023. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Similarly, prehospital evaluation of stroke patients has been practiced for several years. A systematic review of the use of telemedicine in ambulances for stroke patients demonstrated feasibility, reliability, and accuracy in neurological evaluations through telemedicine [35].…”
Section: Telemedicine and Icu Care Outside The Icumentioning
confidence: 99%
“…Similarly, prehospital evaluation of stroke patients has been practiced for several years. A systematic review of the use of telemedicine in ambulances for stroke patients demonstrated feasibility, reliability, and accuracy in neurological evaluations through telemedicine [35].…”
Section: Telemedicine and Icu Care Outside The Icumentioning
confidence: 99%